Preliminary results of Calcium atom analysis by the wind-temperature-metal-constituents LiDAR at Mohe middle-upper atmosphere for the Phase II of Chinese Meridian Project - Fenglei Chen; Yuchang Xun; Zelong Wang; Lifang Du; Haoran Zheng; Zhiqing Chen; Xuewu Cheng; Jiqin Wang; Fang Wu; Guotao Yang (地球与行星物理论评, 2024)
The Phase II of Chinese Meridian Project atmosphere wind-temperature-metal-constituents LiDAR at Mohe (122°E, 53°N) station uses a resonance fluorescence scattering mechanism to detect the metal layer composition in the upper atmosphere at 80-120 km , and subsequently uses these metal components as tracers to study various complex chemical and kinetic processes in the middle and upper atmosphere. The time resolution of this LiDAR is 1.1 min and the spatial resolution is 30 m. With high spatial and temporal resolution, we obtained a high signal to noise ratio for Ca number density. Further, we analyzed the evolution of Ca number density with time and height in January 2023. We observed that the peak value of background and sporadic Ca number densities reached approximately 33.55 cm−3 and 53.64 cm−3, respectively. In comparison with that in Yanqing (116.0°E, 40.5°N) station, the Ca number density in Mohe station was higher. Moreover, while examining the Ca observation studies conducted at foreign stations, we found that the Ca number density in Mohe was close to that of Kuhlungsborn station (54°N, 12°E; Germany) and was higher than that of Observatoire de Haute Provence station (44°N, 6E; France). Additionally, during January 12–14, 2023, we observed calcium meteor trails, consistently appearing near the peak of the metal layer spectrum.